(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
If we pay attention to the development trends of the economies of the world countries, as an important factor in the development of the regions, the expansion of the tax revenue bases of their local budgets is of great importance, ensuring comprehensive and balanced development, rational use of the available natural raw materials, production and labor potential of the regions, and the standard of living of the population. and well-being, as well as consistent continuation of systematic measures to strengthen the budget revenues of local authorities, play an important role in ensuring the economic stability of regions.